Sapatonices em foco: explorando narrativas sapatonas em curtas-metragens brasileiros - Santos, Jaqueline Aparecida dos (Universidade Federal de São Carlos, 2024)
This dissertation analyzes contemporary Brazilian short films whose narrative focus is on lesbian and slut experiences. The research investigates how cinematographic forms are appropriated for the production of slutty subjectivities and the creation of audiovisual content that addresses these themes, breaking with classic and cisheteronormative standards. This is based on an investigation of the narrative forms that develop in relation to the regime of visualities and the constitution of their own images, which escape the policies of control and surveillance of bodies. In this context, bodies are used as tools for documenting and affirming existence. This work is based on comparative analyses of short films, highlighting the creation of new limits of representation that reinforce deviant practices based on a policy of affirming differences, disorganizing cisheterosexual institutions on screen.
Butch tales in focus: exploring lesbian narratives in brazilian short films
Keywords: Cinema sapatão; Curtas-metragens brasileiros; Análise fílmica; Lesbianidades; Sapatonices; Dyke cinema; Brazilian short films; Film analysis; Lesbianities; Dykeness; Dyke-ish; Cinema queer; Tortillera; Cine lésbico; Cortometrajes brasileños; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA; LINGUISTICA, LETRAS E ARTES::ARTES::ARTES DO VIDEO; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::INTERPRETACAO CINEMATOGRAFICA; OUTROS::ESTUDOS SOCIAIS